Real-world annualized healthcare utilization and expenditures among insured US patients with acute intermittent porphyria (AIP) treated with hemin. (2nd June 2020) - Blaylock, Barbara; Epstein, Josh; Stickler, Paul
Abstract: Background and aims: Patients with acute intermittent porphyria (AIP) may suffer from acute non-specific attacks that often result in hospitalizations or emergency room (ER) visits. Prior to the recent approval of givosiran (November 2019), hemin was the only FDA-approved therapy for AIP attacks in the US. Our aim was to estimate the annual healthcare utilization and expenditures for AIP patients treated with hemin using real-world data. Methods: Patients with ≥1 hemin claim and confirmed AIP diagnosis – 1 inpatient claim or 2 outpatient claims ≥30 d apart for AIP (2015–2017) or acute porphyria (prior to 2015) – were identified in MarketScan administrative claims dataset between 2007 and 2017. Continuous enrolment for ≥6 months from confirmed diagnosis was required. A secondary analysis ("active disease population") limited the sample to adult patients with ≥3 attacks or 10 months of prophylactic use of hemin within a 12-month pre-index period. AIP-related care was defined by hemin use during an attack (daily glucose and/or hemin use) or prophylaxis (non-attack hemin use). Outcomes were annualized and expenditures were inflated to 2017. Results: Across 10 years, patients with a confirmed AIP diagnosis ( N  = 8, 877) and ≥1 hemin claim ( N  = 164) were restricted by ≥6 months continuous follow-up ( N  = 139). AIP patients were mostly female ( N  = 112; 81%), had median age of 40 and 3 years average follow-up. Annualized average total expenditures for AIP-related care were $113, 477. Annualized average all-cause (any diagnosis) hospitalizations were statistically significantly lower for patients treated with hemin prophylaxis vs. acute treatment (1.0 vs. 2.1; p  < .001). In the secondary analysis ( N  = 27), annualized average total expenditures for AIP-related care were higher ($187, 480). Conclusions: For AIP patients treated with hemin, patients treated for acute attacks may use a greater number of resources compared to patients treated prophylactically.